Bioassessment of Batang Kandis River Water Quality Using Macrozoobenthos in Koto Tangah district, Padang City - Mhd Nur Allatif; Izmiarti Izmiarti; Nofrita Nofrita (Universitas Andalas, 2021)
This study was conducted from July to December 2019 which was aimed to determine the composition of macrozoobenthic community and to assess the water quality of the Batang Kandis river based on the BMWP ASPT index. A survey method was used in this study. The study site was determined by purposive sampling based on environmental condition which was divided into four stations. Macrozoobenthos samples were taken using a surber net (30 x 30 cm2). The physical and chemical factors of water condition were measured during sampling time. The results showed that 23 genera of macrozoobenthic communities were found in the Batang Kandis river which were consisted of two classes i.e., Hirudinea (1 order, 1 family, 1 genus) and Insect (7 orders, 14 families, 22 genera). These macrozoobenthic communities had an average density ranges from 220.00 - 706.67 ind. m-2 with the highest density was found at Station II and the lowest one at Station IV. Variation in the predominant genus was found at every station: Orthocladius and Elophila (station I); Polypedilum, Orthocladius, Elophila, and Hydropsyche (station II); Polypedylum, Macropelopia, and Caenis (station III); and Polypedylum, Orthocladius, and Caenis (station IV). The water quality of Batang Kandis river was classified into not polluted (station I, II and III) to slightly polluted (station IV) based on the BMWP-ASPT indexes.